PERBAIKAN GIZI REMAJA BERBASIS SEKOLAH DI SMA NEGERI 15 MAKASSAR - Citra Kesumasari; Yessy Kurniati; Djunaidi Machdar Dachlan; Aminuddin Syam; Devintha Virani (LP2M Universitas Hasanuddin, 2019)
Abstract. Improvement of school-based nutrition is important to do, considering students are the nation's next generation. One of the efforts is through balanced nutrition education. The purpose of this activity is to increase the knowledge about the balanced nutrition for students and school members of State High School 15 Makassar, South Sulawesi. The activities were carried out by fully involving the target audience, starting from balanced nutrition education activities in adolescents, demonstrations on determining the nutritional status of adolescents, and discussions. The results of the activities indicate that there has been an increase in knowledge about balanced nutrition in the target audience in accordance with the predetermined indicators of success.Keywords: Teenagers, nutrition, canteen, teacher, students, balancedAbstrak. Perbaikan gizi berbasis sekolah penting untuk dilakukan, mengingat siswa merupakan generasi pelanjut bangsa. Salah satu upaya tersebut adalah melalui edukasi gizi seimbang. Tujuan kegiatan ini adalah meningkatkan pengetahuan tentang gizi seimbang pada siswa dan warga sekolah di SMA Negeri 15 Makassar, Sulawesi Selatan. Kegiatan dilaksanakan dengan melibatkan secara penuh khalayak sasaran, mulai dari kegiatan edukasi gizi seimbang pada remaja, demonstrasi penentuan status gizi remaja dan diskusi. Hasil kegiatan menunjukkan telah terjadi peningkatan pengetahuan tentang gizi seimbang pada khalayak sasaran sesuai dengan indikator keberhasilan yang telah ditetapkan.Kata Kunci: Remaja, gizi, kantin, guru, siswa, seimbang